Defining Age-related OSA Features in Robin Sequence Using Polysomnographic-based Analyses of Respiratory Arousal Responses and Gas-exchange Parameters. (February 2023) - Nino, Gustavo; Aziz, Julia; Weiss, Miriam; Allen, Michelle; Lew, Jenny; Manrique, Monica; Mantilla-Rivas, Esperanza; McGrath, Jennifer L.; Rogers, Gary F.; Oh, Albert K.
Introduction: Robin sequence (RS) is a leading cause of obstructive sleep apnea (OSA) in newborns. Most studies have focused on understanding anatomic factors leading to OSA and changes in apnea–hypopnea index (AHI) on polysomnography (PSG) beyond the neonatal period. This study aims to define age-related OSA features between patients with RS, without RS and healthy controls using PSG-based analyses of respiratory arousal responses and gas-exchange parameters. Design: Retrospective comparison of PSG features in a total of 48 children encompassing three groups: (a) infants with RS (n = 24, <1-year old), (b) non-RS older children (1-2 years old) with severe OSA (obstructive AHI (OAHI) of ≥10 events; n = 12), and (c) control infants and children (0-2 years old) without sleep apnea (OAHI ≤1.5/h, n = 12). We examined OSA sleep-stage specific and position-specific indexes, and the relationship between OSA severity and respiratory arousal indexes (OAHI/respiratory arousal indexes). Results: OSA sleep-stage specific indexes (rapid eye movement [REM] vs non-REM[NREM]) as well as position-specific indexes (supine vs nonsupine) were similar in individuals with and without RS. Relative to the non-RS groups, infants with RS have more sustained hypoxemia (time with SpO2 < 90%) and reduced arousal responses to OSA demonstrated by higher OAHI/respiratory arousal indexes. OAHI/respiratory arousal indexes significantly correlated with the severity of hypoxemia in infants with RS. Conclusion: Infants with RS and OSA show reduced arousal responses to apneic events, which correlates with higher hypoxemia severity. OAHI/respiratory arousal indexes in RS may identify high-risk individuals with upper airway obstruction and reduced arousal protective responses.